Pengaruh Persepsi, Promosi Dan Pengetahuan Terhadap Keputusan Menjadi Nasabah Deposito Pada PT BPR BKK Purworejo (Perseroda) Cabang Bayan - Suhartini, Titik; Wulanda , Riska (Jurnal Ilmiah Raflesia Akuntansi, 2024)
PT BPR BKK Purworejo (Perseroda) Bayan Branch is a financial institution established based on the Decree of the Governor of the Regional Head of Level I Central Java. This bank has received permission from the Financial Services Authority (OJK) and the Deposit Insurance Corporation (LPS). The influence of perception, promotion and knowledge aims to find out how much influence customers have in depositing their funds. The data used in this research is qualitative and quantitative. The methods used are interviews and observation.This research aims to determine the influence of perception, promotion and knowledge on the decision to become a deposit customer at PT BPR BKK Purworejo (Perseroda) Bayan Branch. The population in this study were deposit customers at PT BPR BKK Purworejo (Perseroda) Bayan Branch with a sample size of 30 people. The instrument used in this research is a questionnaire on the decision to become a deposit customer which has previously been tested and has met the validity and reliability requirements, while data analysis uses multiple regression analysis. The results of this research show that: the results of the t test analysis on the perception variable show that the significant value is greater than 0.05, namely 0.609 > 0.05, which does not have a significant effect on the decision to become a deposit customer. The results of the t test on the promotion variable show that the significant value is greater than 0.05, namely 0.146 > 0.05, which does not have a significant effect on deposit customer decisions. The results of the t test on the knowledge variable show that the significant value is smaller than 0.05, namely 0.012 <0.05, there is a significant influence on the decision to become a deposit customer. The results of the F test analysis show that the F test value is 3.565 with a significant amount of 0.028, less than 0.05, meaning that the variables of perception, promotion and knowledge have a significant influence on the decision to become a deposit customer at PT BPR BKK Purworejo (Perseroda) Bayan Branch.